China baseline coal-fired power plant with post-combustion CO2 capture: 2. Techno-economics. (November 2018) - Singh, Surinder; Lu, Haoren; Cui, Qian; Li, Chufu; Zhao, Xinglei; Xu, Wenqiang; Ku, Anthony Y.
Highlights: Baseline power plant models are essential for understanding the cost of CO2 capture. Power plants in China have distinct hardware and operating conditions, as well as financing conditions. The cost drivers for a set of "baseline China plants with CO2 capture" are proposed. The biggest driver is capital cost, but other important factors have been identified Other important drivers include plant utilization, fuel and operating costs. Abstract: Global efforts to advance CO2 capture technologies have produced a strong base of field experience and modeling capability to inform efforts to deploy this technology. In China, there are some important features of power plant construction, operation, and financing that lead to lower costs of CO2 capture relative to the United States and the most of the rest of the world. Moreover, unique aspects of the policy landscape in China, such as an openness to partial capture solutions in the near-term, allow for flexibility in deployment strategy. In this study, we define a set of "China baseline" reference cases and use them to analyze the costs of retrofit post-combustion CO2 capture at supercritical coal-fired power plants in China. We find the cost of post-combustion CO2 capture from power plants in China ranges from about 260 to 280 RMB/tCO2 (40–43 USD/tCO2) captured and 390 to 480 RMB/tCO2 (60–74 USD/ tCO2 ) avoided. This is at the higher end of the range of published literature estimates for China, but significantly lower than the corresponding ranges in the US for nominally the same technological approach. Lower costs in China have been primarily ascribed to lower capital costs, but a clear analysis of the full set of drivers for cost differences has not yet been published. Our analysis confirms the importance of capital savings, identifies the contributions from other significant factors such as fuel costs and power plant utilization, and explores several strategic implications for how these cost drivers might impact the deployment of CCS in China.